Module for the psychological assessment of the mental and emotional state of the medical staff during the COVID-19 pandemic - Hamada, E. A.; Selim, T. M. (Boston, USA, 2020)
In this paper, we developed a program module for the automated testing mental and emotional state of medical health workers for verifying whether allostatic overload develops (exhaustion may ensue after some time) and whether psychiatric disorders, especially posttraumatic stress disorder, might occur with the COVID-19 progression. Psychological assessment was based on an online survey and on self-report tool
Keywords: module; medical staff; allostatic overload; psychological testing